Ideal geometries in the military architecture of F. di Giorgio Martini. The defence system fortress-tower of Cagli - Paolo Clini; Ramona Quattrini; Daniela Amadei; Romina Nespeca (Disegnare con)
The subject of the military architecture was widely studied and analyzed by the architect Francesco di Giorgio Martini (1439-1501), who created important defensive works in the duchy of Montefeltro. A defensive line connects a series of medieval villages of the Marches: b Between the Martini’s fortifications, Cagli has still a fortified tower perfectly preserved and some traces of the fortress. The analysis conducted on them involves the information inferable by the essay, by historical surveys and the recent laser scanner survey. The aim of the research was to identify the generating geometry of the architecture: taking the precepts of Vitruvius, in the Renaissance period geometry was synonymous with proportion, order and symmetry. Two are subjects: the first one is the in-depth knowledge of the tower through the digital data obtained from the point cloud, the other one is the reconstruction of a global image of the complex tower-fortress.